Find trusted answers to your questions with the help of IDNLearn.com's knowledgeable community. Ask your questions and get detailed, reliable answers from our community of experienced experts.

Convert the following system of equations into an augmented matrix: (1) 2x + 2y + 2z = 4(2) -x − 3y = 2 + 8z − 3y(3) -z = 2x + y

Sagot :

ANSWER and EXPLANATION

We want to transform the system of equations given into an augmented matrix.

First, we have to put the equations in the form:

[tex]\begin{gathered} a_1x+b_1y+c_1z=k^{} \\ a_2x+b_2y+c_2z=l \\ a_3x+b_3y+c_3z=m \end{gathered}[/tex]

where k, l, and m are constants

a1, a2, a3, b1, b2, b3, c1, c2, and c3 are coefficients of x, y, and z in the equations

Therefore, we have that the equations become:

[tex]\begin{gathered} \Rightarrow2x+2y+2z=4 \\ -x-3y+3y-8z=2 \\ \Rightarrow-x-8z=2 \\ \Rightarrow2x+y+z=0 \end{gathered}[/tex]

The augmented matrix will be in the form:

From the above equations, we have that the coefficients and constants are:

[tex]\begin{gathered} a_1=2;b_1=2;c_1=2;k=4 \\ a_2=-1;b_2=0;c_2=-8;l=2 \\ a_3=2;b_3=1;c_3=1;m=0 \end{gathered}[/tex]

Therefore, the augmented matrix is:

View image EugenieH418537
View image EugenieH418537
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. Your questions deserve precise answers. Thank you for visiting IDNLearn.com, and see you again soon for more helpful information.